Pengelolaan Filantropi Islam untuk Pendidikan dan Pengentasan Kemiskinan (Menuju Tata Kelola Dana Filantropi untuk Kemanusiaan) - Aziz, Muhammad; Rahman, Clarita Ise Afifatunnisa (Al Hikmah: Jurnal Studi Keislaman, 2022)
Abstract, Zakat as an Islamic economic instrument is expected to be a bridge between the rich and the poor to overcome the problem of poverty. However, the reality has become a polemic that is still interesting to talk about where from year to year there are always incidents related to zakat, including the habit of jostling at Muzakki's house just for twenty thousand rupiahs. This research is included in the category of field research. The approach is juridical-normative. The data collection uses; a). Observation; b). Interview; c). Documentation. While processing the data through several stages; Editing, Classifying, Verifying, Analysing, Closing. The results of this study are that Islamic philanthropic activities that have been carried out by the Amil Zakat Nurul Hayat Institute, Tuban Branch, through several activities and stages, including; Independent Pillar Program, Education Scholarship Establishment of superior formal education. All of these programs are funded from philanthropic fundraising carried out by Nurul Hayat Tuban, in the form of zakat, infaq, shaqadah and others. The implications of Islamic philanthropic activities that are socially included in the field of poverty alleviation activities and strengthening superior education for the younger generation of Muslims, is proof that Islamic philanthropy, if managed properly, will be part of the Islamic instrument solution in the field of community economic management, which will later can make people more empowered and stronger, both educationally and economically.